Pain reduction in patients after applying a nitrous oxide/oxygen mixture (Livopan) during photodynamic therapy: study protocol for an observational study (Livopan study) - Gholam, Patrick; Müller-Christmann, Christine; Uhlmann, Lorenz; Enk, Alexander (BMJ open, 2015)
Introduction Photodynamic therapy (PDT) is an effective treatment option for extensively photodamaged skin with multiple actinic kerastosis. However, the main drawback of PDT is the intensive pain experienced during its application, which makes it frequently necessary to interrupt or even terminate the process resulting in incomplete treatment. Several strategies for controlling pain during PDT have been studied but few effective methods are currently available. Alternative options are urgently needed. Livopan, a nitrous oxide/oxygen mixture, is indicated for the treatment of short-term pain conditions when rapid analgesic onset and offset effects are wanted. But so far, there are no studies evaluating the effect of Livopan on pain intensity during PDT. Therefore, it remains unclear whether patients benefit from this inhalation analgesia. Within the Livopan study, this issue will be evaluated for the first time. - Methods and analysis The Livopan study is a prospective, single-centre, explorative, controlled, observational study to investigate the pain reduction in patients after applying a nitrous oxide/oxygen mixture (Livopan) during PDT according to the visual analogue scale in 60 patients. - Ethics and dissemination Ethics approval was provided by the ethics committee of the medical faculty of the University of Heidelberg. Ethics approval number S-169/2014. - Trial registration number German Clinical Trial Register (DRKS): DRKS00006054.